Optimasi Penggunaan Hidrogen Peroksida (H2O2) Terhadap Penurunan Kadar Sianida Pada Limbah Cair - Muntasir Muntasir; M. Sjahrul; Muhammad Zakir; Indah Raya (Al-Kimia, 2015)
Optimation studies have been conducted using hydrogen peroxide (H2O2) to the reduction of cyanide levels in the wastewater. Parameters studied were the optimum concentration of hydrogen peroxide (H2O2), the optimum pH and optimum contact time between hydrogen peroxide (H2O2) with wastewater in reducing the cyanide content. Cyanide obtained from steam distillation of liquid waste and the assay using 0.02N silver nitrate. Concentration used were 500 ppm, 400 ppm, 300 ppm, 200 ppm and 100 ppm; pH range is (7, 8, 9, 10 and 11) and the variation of the contact time is: 0, 30, 60, 90, 120 and 150 minutes. The result of the research reveals at early treatment the cyanide content is 50,22% w / w and underwend a reduction in levels after addition of various concentrations of H2O2; variations in pH variation of contact time. Optimum condition treatment at 500 ppm of H2O2  basicity at pH 8 and contact time for 60 minutes result reduction of cyanide level of 36,40% w/w, 40,91% w/w and 37,09% w/w respectively.